2018
DOI: 10.1016/j.bar.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Topics and trends in finance research: What is published, who publishes it and what gets cited?

Abstract: In this study we provide a detailed examination of the subject matter of finance research and its institutional features as it has evolved over the past two decades. Drawing on novel approaches from data science, we examine the content of more than 30,000 published papers. Overall, we find a striking lack of diversity in the topics investigated and the methodological approaches used. Almost all finance research is conducted using techniques from economics and mathematics, with virtually no use made of qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 66 publications
(76 reference statements)
2
16
0
1
Order By: Relevance
“…These findings of increasingly homogenised research designs of finance publications in the 'top' journals correspond well to the results of a recent study of more than 30,000 papers published in finance which revealed that less than one percent of the work examined represents qualitative research such as interviews, case studies, or experiments (Brooks & Schopohl, 2018). In addition, the study shows that only a very small proportion of the studies could be classified as interdisciplinary (taking ideas or methodologies from other fields), in contrast to other subject areas in social science.…”
Section: <Insert Table 3 About Here>supporting
confidence: 84%
See 4 more Smart Citations
“…These findings of increasingly homogenised research designs of finance publications in the 'top' journals correspond well to the results of a recent study of more than 30,000 papers published in finance which revealed that less than one percent of the work examined represents qualitative research such as interviews, case studies, or experiments (Brooks & Schopohl, 2018). In addition, the study shows that only a very small proportion of the studies could be classified as interdisciplinary (taking ideas or methodologies from other fields), in contrast to other subject areas in social science.…”
Section: <Insert Table 3 About Here>supporting
confidence: 84%
“…Although our focus in this study is on the 'elite' journals, Brooks & Schopohl (2018) provide evidence that the broad subject areas within finance (e.g., asset pricing versus corporate finance), and even the narrower topics within each of these areas, are fairly similar across journals with different ABS list ratings. In addition, they show that the use of methodological approaches other than the quantitative empirical analysis of datasets (e.g., surveys or interviews, case studies, experiments) takes place in just over 1% percent of published papers.…”
Section: The Research Published In Finance Journalsmentioning
confidence: 99%
See 3 more Smart Citations